Benign fasciculations and Corticosteroid use: possible association? An update - Marco Orsini; Flavio R. Sztajnbok; Acary Bulle Oliveira; Marco Antonio Araújo Leite; Peter Salem Júnior; Marcos R.G. de Freitas; Osvaldo J.M. Nascimento; Júlio Guilherme Silva; Marzia Puccioni Sholer; Fernando Silva Guimarães; Alessandra Cardoso Pereira; Sara Lúcia Silveira de Menezes; et al. (MDPI AG, 2011)
Fasciculations are characterized by visible subtle and fast contractions of muscle, even wormlike in movement, by the contraction of a fascicle of muscle fibers. The authors present the case study of a 28-year-old patient with the appearance of migratory and diffuse fasciculations with an onset after partial tapering off of oral corticosteroides (60 mg total dose) indicated for treatment of Minimal change Glomerulopathy. Clinical Neurological physical exam allied with an ENMG, besides other complementary laboratory exams were used for screening the above-mentioned patient. Afterwards, current research relating to the topic at hand was made in order to update the data available in the Bireme, Scielo and PubMed Data Banks using the following key words: Fasciculation's, motor neuron disease, and benign fasciculations in the Portuguese, English as well as Spanish language. Although fasciculation's are most commonly associated with Motor neuron disease as well as with certain metabolic disorders, they may also be present in individuals with absolutely no underlying pathological disorders. In our case, fasciculation potentials that have been present for six months, with no other signs of a neurogenic disorder as well as absence of laboratory findings, the patient received a diagnosis of Benign Fasciculation Syndrome (BFS).We believe that the use of corticosteroides in high doses with subsequent tapering contributed to the fasciculation's, especially due to the changes that this causes on the ionic channels. Fasciculation's are symptoms seen in a large range of conditions, and also being the main symptom of the so-called Benign Fasciculation Syndrome. We have presented an example of this clinical syndrome in a patient whose complaint was fasciculation's, with complete clinical remission of symptoms following complete tapering off of corticosteroid six months previously.